2019
DOI: 10.1093/mnras/stz2799
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the post-reionization neutral hydrogen (H i) 21-cm bispectrum

Abstract: Measurements of the post-reionization 21-cm bispectrum B HI (k 1 , k 2 , k 3 ) using various upcoming intensity mapping experiments hold the potential for determining the cosmological parameters at a high level of precision. In this paper we have estimated the 21-cm bispectrum in the z range 1 z 6 using semi-numerical simulations of the neutral hydrogen (HI) distribution. We determine the k and z range where the 21-cm bispectrum can be adequately modelled using the predictions of second order perturbation theo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 119 publications
(96 reference statements)
0
10
0
Order By: Relevance
“…[21] found that upcoming 21-cm surveys could be able to measure the FDM particle mass as high as 10 −18 eV, which would be interesting to revisit under the inclusion of additional heating effects. The higher order statistics, like the bispectrum [88][89][90][91], trispectrum [92] etc., if measured with high accuracy, will provide us with more constraining power. We leave these for future study.…”
Section: Discussionmentioning
confidence: 99%
“…[21] found that upcoming 21-cm surveys could be able to measure the FDM particle mass as high as 10 −18 eV, which would be interesting to revisit under the inclusion of additional heating effects. The higher order statistics, like the bispectrum [88][89][90][91], trispectrum [92] etc., if measured with high accuracy, will provide us with more constraining power. We leave these for future study.…”
Section: Discussionmentioning
confidence: 99%
“…[62]. Other possible strategies include the combination with other cosmological probes [56] or joint analyses of two-point and higher order statistics measurements [80,81].…”
Section: Discussionmentioning
confidence: 99%
“…[80] in the case of halo number counts, and Ref. [81] for the 21cm LIM case); multi-tracer techniques with several spectral lines and galaxy surveys [56]; or the exploitation of the mildly non-linear regime of the LIM power spectrum by modelling the halo clustering with Lagrangian perturbation theory [62].…”
Section: Explicitly Accounting For the Degeneraciesmentioning
confidence: 99%
“…Unlike the power spectrum, the bispectrum is sensitive to the shape of the structures generated by gravitational instability and has the promise to break important degeneracies in the bias and cosmological parameters (Scoccimarro 2000;Sefusatti et al 2006;Hahn et al 2020;Yankelevich & Porciani 2019;Chudaykin & Ivanov 2019). The post-reionization 21cm signal is expected to have significant information in the non-linear regime and there have been recent attempts at theoretical modeling of the Hi bispectrum (Sarkar et al 2019). One of the toughest parts in a bispectrum analysis is calculation of the error due to cosmic variance and a fast technique to generate mock Hi fields is therefore essential.…”
Section: Cross-correlation With Galaxies and Halosmentioning
confidence: 99%